Active recycling of yeast Golgi mannosyltransferase complexes through the endoplasmic reticulum - Todorow, Zlatko (The National Academy of Sciences, 2000)
Mnn9p is a component of two distinct multiprotein complexes in the Saccharomyces cerevisiae cis-Golgi that have both been shown to have α-1,6-mannosyltransferase activity in vitro. In one of these complexes, Mnn9p associates with four other membrane proteins, Anp1p, Mnn10p, Mnn11p, and Hoc1p, whereas the other complex consists of Mnn9p and Van1p. Members of the Mnn9p-containing complexes were incorporated into COPII vesicles made in vitro from endoplasmic reticulum (ER) membranes isolated from cycloheximide-treated cells. This behavior is consistent with an active Golgi to ER recycling process. To examine this path in vivo, we monitored retrograde transport of subunits of the complex in cells blocked in anterograde transport from the ER. In this situation, specific relocation of the proteins from the Golgi to the ER was observed in the absence of new protein synthesis. Conversely, when retrograde transport was blocked in vivo, subunits of the mannosyltransferase complex accumulated in the vacuole. Packaging of Mnn9p in COPI-coated vesicles from purified Golgi membranes was also investigated using a coatomer-dependent vesicle budding assay. Gradient fractionation experiments showed that Mnn9p and the retrograde v-SNARE, Sec22p, were incorporated into COPI-coated vesicles. These observations indicate that the Mnn9p-containing mannosyltransferase complexes cycle back and forth between the ER and Golgi.